Bulgaria : Staff Report for the 1999 Article IV Consultation and Third Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2000)
In 1999, Executive Board deliberations on Bulgaria focused on the need for the authorities to persevere with structural reform. Under the currency board arrangement introduced in mid-1997, Bulgaria has achieved macroeconomic stabilization and made substantial progress in structural reform. Banking supervision has improved markedly. Executive Directors stressed the importance of wage moderation and flexible labor markets for maintaining competitiveness and reducing unemployment. The emerging private sector also faces many obstacles, including burdensome bureaucracy and red tape, weak governance, and a banking system hesitant to extend credit.